Sepsis of early beginning in the preterm newborn - Rafael Ferrer Montoya; Alfredo Jiménez Noguera; Alina Vázquez Estrada; María Cristina Cedeño Esturo (Centro Provincial de Información de Ciencias Médicas, 2020)
The sepsis is a potentially mortal disease that can affect the newborn. In such a sense, the necessary information is exposed to offer an appropriate care to the preterm newborn with sepsis of early beginning: concept, epidemiology, pathogenesis, clinical signs, diagnosis, treatment and prevention. Also, some factors that increase the infection possibility in this newborn, the predisposing conditions in the mother and the chorioamnionitis (clinical and histological) are approached. This infection can be prevented by means of an appropriate prenatal control and a correct care during the childbirth, which will diminish the morbidity and mortality, as well as will have great impact in the public health of the country.